A new species of Mimosa section Mimosa (Leguminosae) from the Paraguayan Cerrado - Morales, Matías; Grohar, Mariana C.; Rosenfeldt, Sonia; Fortunato, Renée H. (Phytotaxa, 2019)
Mimosa schininii (Leguminosae), a new species from the Amambay region, in the Cerrado ecoregion of northeastern Paraguay, is described and illustrated. This new species belongs to Mimosa L. section Mimosa series Mimosa subseries Brevipedes Barneby, and is similar to M. brevipes Benth. and M. sceptrum Barneby, but differs from them by shorter inflorescence, secondary leaflets venation pattern and fruit dehiscence. This new entity resembles, in some characters, other subseries of series Mimosa, such as Mimosa section Mimosa series Mimosa subseries Pedunculosae (Benth.) Barneby and Hirsutae (Benth.) Barneby, but can be distinguished adequately from them by vegetative, floral, and carpological characters. Illustration, distribution map, and a key to distinguish M. schininii from close relatives are provided.